Lower genomic stability of induced pluripotent stem cells reflects increased non‐homologous end joining. Issue 1 (25th July 2018) - Zhang, Minjie; Wang, Liu; An, Ke; Cai, Jun; Li, Guochao; Yang, Caiyun; Liu, Huixian; Du, Fengxia; Han, Xiao; Zhang, Zilong; Zhao, Zitong; Pei, Duanqing; et al.
Abstract: Background: Induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs) share many common features, including similar morphology, gene expression and in vitro differentiation profiles. However, genomic stability is much lower in iPSCs than in ESCs. In the current study, we examined whether changes in DNA damage repair in iPSCs are responsible for their greater tendency towards mutagenesis. Methods: Mouse iPSCs, ESCs and embryonic fibroblasts were exposed to ionizing radiation (4 Gy) to introduce double‐strand DNA breaks. At 4 h later, fidelity of DNA damage repair was assessed using whole‐genome re‐sequencing. We also analyzed genomic stability in mice derived from iPSCs versus ESCs. Results: In comparison to ESCs and embryonic fibroblasts, iPSCs had lower DNA damage repair capacity, more somatic mutations and short indels after irradiation. iPSCs showed greater non‐homologous end joining DNA repair and less homologous recombination DNA repair. Mice derived from iPSCs had lower DNA damage repair capacity than ESC‐derived mice as well as C57 control mice. Conclusions: The relatively low genomic stability of iPSCs and their high rate of tumorigenesis in vivo appear to be due, at least in part, to low fidelity of DNA damage repair.